Sazonalidade climática e dinâmica populacional de Lanio pileatus (Aves: Passariformis) em um semiárido Neotropical - Moura, Pedro Teófilo Silva de (Universidade Federal Rural do Semi-Árido, 2016)
Variations in bird abundance species are associated with variation in food availability or effects of seasonality in these populations. As the Caatinga a tropical semi-arid environment with seasonal characteristics, assuming that local climate regime is able to act on demographic parameters of bird populations in semi-arid environments, our hypothesis is that intra and interannual variations in the abundance of Lanio pileatus are determined ultimately by precipitation regime. In this way we hope that (1) the precipitation is a variable predictor of reproductive intensity in intra and interannual levels, (2) the intensity of reproduction is one predictor of temporal variation in the abundance of young, (3) the temporal variation in the input individuals the population is predicted by temporal variation in the abundance of young and (4) population survival L. pileatus is inversely related to rainfall, and the rainfall determinants of intra and interannual periods of higher output (mortality) of individuals in the population. The birds were captured in a Caatinga area inserted in the ecoregion of the Depressão Sertaneja Setentrional with the mist nets from September 2012 to September 2015. We analyzed the data in the Mark program using the POPAN model to estimate apparent survival, probability of capture, probability of entrance and population size. The covariates entered in our analysis were: time, year, rainy season, breeding, brood patch and juvenile occurrence period independently and a constant model. On this study recorded 411 captures and 295 recaptures L. pileatus on 78 occasions sampling over the three years of study. During this period the reproduction of the species has always coincides with the rainy season. The analysis using Mark program demonstrated a pattern of exponential growth in the L. pileatus population. The results of the average model for the set of candidate models have shown effects of environmental seasonality on estimates of apparent survival, as well as a relationship between the new individuals entering the population and the reproductive period, generating a cyclical fluctuation of the population size
Keywords: Coryphospingus pileatus; Semiárido; POPAN; Abundância; Ecologia de populações; Coryphospingus pileatus; Semi-arid; POPAN; Abundance; Population Ecology; CIENCIAS BIOLOGICAS::ECOLOGIA